Pengaruh Kecerdasan Spiritual dan Literasi Keuangan Terhadap Manajemen Keuangan Pribadi: (The Influence of Spiritual Intelligence and Financial Literacy on Student Personal Financial Management) - Ika Yustina Rahmawati; Artika Cahyaningsih; Cicih Wiarsih (UPT Penerbitan Universitas Jember, 2023)
The research aims to find out how student personal financial management is influenced by spiritual intelligence and financial literacy. Purposive sampling technique was used to select the sample for this investigation. Students of the Faculty of Economics and Commerce Muhammadiyah University Purwokerto, Jenderal Soedirman University, and Saiffudin Zuhri State Islamic University Purwokerto became the population of this study. 110 participants sampled for this investigation. Multiple regression analysis, classical assumption test, model fit test, and descriptive statistical analysis were used to evaluate the data. The findings from the results are that financial literacy and spiritual intelligence have a beneficial impact on personal financial management.